The effect of an eight-week proprioception training program on agility, quickness and acceleration - Taşkın, Cengiz; Bıcer, Yonca Sureyya (My University, 2015)
The effect of an eight-weeks proprioception training programme on agility, quicknessand acceleration in this study which aims at determining the effect of an 8-weeks proprioceptive training on agility, quickness and acceleration, 13 students studying at the school of physical education and sports, aged 23.46 ± 2.57 on average, participated as an experimental group. 13 students studying at the school of physical education and sports, aged 22.39 ± 1.56 on average, also took part in this study as a control group. In the training program for developing proprioception, a multi-directional, inclined balance board was used for anterior/posterior, lateral/medial, clockwise and anti-clockwise movements. An eight-weeks training program, which comprised of 5 sec warm-up, 20 sec proprioceptive training and 5 sec cooling in a day, was performed for total 30 second for 3 days in a week. The first 5 meters for quickness, 10 and 15 meters for acceleration and for t-test for agility were considered, the measurements were obtained as pre-test and post-test ones. For the experimental group, before and after the training, the values were measured as 5 meters for quickness, 10 and 15 meters for acceleration and 1.09±0.05 sec and 1.03±0.05 sec, 1.92±0.11 sec and 1.80±0.11 sec, 2.61±0.12 sec and 2.48±0.08 sec, 10.69±0.64 sec and 10.13±0.35 sec for agility respectively. When compared to the values of quickness, acceleration and agility for the experimental group, a significant difference was found out (P<0.05). For the control group, before and after the training, the values were also given as 5 meters for quickness, 10 and 15 meters for acceleration and 1.05±0.08 sec and 1.04±0.05 sec, 1.88±0.05 sec and 1.89±0.08 sec, 2.53±0.11 sec and 2.52±0.12 sec, 10.26±0.54 sec and 9.97±0.34 sec for agility respectively. When compared to the values of quickness, acceleration and agility for the control group, no significant difference was found out (P>0.05). In conclusion, it was determined that an 8-weeks proprioceptive training developed the characteristics of quickness, acceleration and agility.
Keywords: Spor Bilimleri